Oathkeeper - Hunter, Erin (Hunter, Erin. Bravelands, 2020)
At long last, the Great Herd is united against Titan -- now so powerful that even Fearless, who vowed to avenge his father's death, cannot defeat the rogue lion alone. Thorn may have a plan to bring about Titan's downfall, but the animals of Bravelands must decide how much they are willing to risk--and who they are willing to lose.